Novel and potent MICA/B antibody is therapeutically effective in KRAS LKB1 mutant lung cancer models - Shohei Koyama; Yujiro Naito; John D Minna; David E Gerber; Ryan R Kowash; Manoj Sabnani; Laura T Gray; Qing Deng; Nusrat U A Saleh; Luc Girard; Kentaro Masahiro; Zhiqian Lucy Liu; et al. (Journal for ImmunoTherapy of Cancer)
Background Concurrent KRAS LKB1 (STK11, KL) mutant non-small cell lung cancers (NSCLC) do not respond well to current immune checkpoint blockade therapies, however targeting major histocompatibility complex class I-related chain A or B (MICA/B), could pose an alternative therapeutic strategy through activation of natural killer (NK) cells.Methods Expression of NK cell activating ligands in NSCLC cell line and patient data were analyzed. Cell surface expression of MICA/B in NSCLC cell lines was determined through flow cytometry while ligand shedding in both patient blood and cell lines was determined through ELISA. We engineered an antibody-dependent cellular cytotoxicity (ADCC) enhanced MICA/B monoclonal antibody, AHA-1031, which prevents ligand shedding without interfering with binding to natural killer group 2D while targeting cancer cells via superior ADCC. We performed in vitro assays using ELISA and flow cytometry-based assays to confirm that our antibody potently binds to and stabilizes MICA/B expression across lung cancer and other solid tumor cell lines. Additionally, we used two KL mutant NSCLC cell lines and a KL mutant patient-derived xenograft (PDX) model to demonstrate in vivo antitumor efficacy and flow cytometry analysis for immune cell activation profiling.Results NSCLC cell lines exhibit high MICA/B expression and secrete soluble MICA/B in vitro. Soluble MICA/B is also detected in patient blood samples. AHA-1031 binds to the α3 domain of MICA/B, preventing shedding and targeting tumor cells to ADCC. AHA-1031 exhibits high affinity and specificity to MICA/B, preventing MICA/B shedding in tumor lines and inducing ADCC in vitro. Our antibody also effectively binds and stabilizes MICA/B expression in additional tumor types and demonstrates broad specificity. We show that in two KL mutant NSCLC xenograft models and a KL mutant PDX model, treatment with AHA-1031 monotherapy significantly inhibits tumor growth compared with vehicle-treated animals with no observable toxicity. Tumor tissues from treated mice exhibit significantly increased immune cell infiltrates and activated NK cell populations.Conclusions Activating NK cells through MICA/B stabilization and inducing ADCC offers an alternative and potent therapy option in KL tumors. MICA/B are shed across different tumors making this therapeutic strategy universally applicable.